MODEL PENCEGAHAN KANKER SERVIKS BERDASARKAN KARATERISTIK SOSIAL BUDAYA PADA WANITADI DESA PAGELARAN KABUPATEN MALANG - Harini, Ririn (Jurnal Kesehatan Mesencephalon, 2018)
The development of prevention efforts to reduce cervical cancer among high risk women is part of maternity nursing and particularly in the field of womens reproductive health care. Applications of nursing and health-care procedures aimed at the conservation, promotion and restoration of individual health and a community group that is part of the effort to develop a model of nursing matenitas. The role of health promotion in this research is to empower the community through awareness raising in the cultural aspects of society. The study was conducted to achieve several objectives, namely to identify cultural characteristics factors, social support factors in women with high risk of cervical cancer, analyzing the forms and media promotion in high risk women with cervical cancer, designing primary and secondary prevention models of cervical cancer and Analyze implementation of primary and secondary prevention in women high risk of cervical cancer. The type of research used in this research is descriptive analytic research. Descriptive analytic research is needed to identify women data with high risk of cervical cancer, cultural factors, and social support factors. The population in the study of 280 women of childbearing age (WUS) in Kab. Poor. The sample used after the measured sample size is 99 fertile age women who married at the age of less than 20 years. The sample was taken by simple random sampling. The results showed that the characteristics of respondents based on predisposing factors in early detection of cervical cancer include age, education, occupation, income, marital status, knowledge and attitude contributed to knowledge and behavior of WUS in preventing the occurrence of cervical cancer. Keywords: Prevention model, cervical cancer, socio-cultural characteristics